Common Fixed Point Theorem of Two Mappings Satisfying a Generalized Weak Contractive Condition - M. Abbas; M. Ali Khan (International Journal of Mathematics and Mathematical Sciences)
Existence of common fixed point for two mappings which satisfy a generalized weak contractive condition is established. As a consequence, a common fixed point result for mappings satisfying a contractive condition of integral type is obtained. Our results generalize, extend, and unify several well-known comparable results in literature.